1998
DOI: 10.2307/3004050
|View full text |Cite
|
Sign up to set email alerts
|

Young unwed fathers of afdc children: do they provide support?

Abstract: We examine the support provided by fathers of children born to disadvantaged teenage mothers. Our sample includes the fathers of 6,009 children born over a two-year period to 3,855 teenage mothers receiving AFDC in three economically depressed inner cities. These fathers provide little social and economic support to their children. Support declines as their children age from infants to toddlers and as fathers' relationships with the mothers grow more distant. Fathers' employment status and educational attainme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 17 publications
6
56
0
1
Order By: Relevance
“…Although often considered as an exogenous variable, most research simply controls for human capital rather than examining the unique contribution it may have on fathering. Adolescent Father Social Capital 5 Overall, the existing literature suggests that finishing high school and securing employment is positively related to the involvement of fathers of children born to adolescent mothers (e.g., Danziger and Radin 1990;Jaffee et al 2001;Rangarajan and Gleason 1998;Wiemann et al 2006). One explanation for this association may be that these accomplishments are related to greater levels of responsibility, familial and community support networks, and competency (e.g., Dearden et al 1992;Fagot et al 1998;Futris and Pasley 2000).…”
Section: Social Capitalmentioning
confidence: 95%
See 2 more Smart Citations
“…Although often considered as an exogenous variable, most research simply controls for human capital rather than examining the unique contribution it may have on fathering. Adolescent Father Social Capital 5 Overall, the existing literature suggests that finishing high school and securing employment is positively related to the involvement of fathers of children born to adolescent mothers (e.g., Danziger and Radin 1990;Jaffee et al 2001;Rangarajan and Gleason 1998;Wiemann et al 2006). One explanation for this association may be that these accomplishments are related to greater levels of responsibility, familial and community support networks, and competency (e.g., Dearden et al 1992;Fagot et al 1998;Futris and Pasley 2000).…”
Section: Social Capitalmentioning
confidence: 95%
“…Although young fathers are not likely to share permanent residency with their child as they grow older, many live with the child and mother during the early years of the child's life (Lerman and Sorensen 2000). For example, various studies on the involvement of young unwed fathers report that approximately 40% of these fathers live with their child during the first 2 years after their child's birth (Coley and Chase-Lansdale 1999;Fagot et al 1998;Jaffee et al 2001;Rangarajan and Gleason 1998).…”
Section: Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies indicated that black and Hispanic fathers were less likely to have been making formal child support payments than white nonresident fathers (Huang, Mincy, and Garfinkel 2005;Smock and Manning 1997). Similarly, fathers with lower educational attainment were shown to have been providing less formal child support than their better educated counterparts (Huang, Mincy, and Garfinkel 2005;Rangarajan and Gleason 1998;Smock and Manning 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Seltzer (2000) finds that nonresident fathers who maintain closer contact with their children are more likely to pay child support, perhaps because they can observe more directly how that money is supporting the child's welfare, which could contribute to better outcomes since child support is a significant positive correlate of children's cognitive development (Argys et al, 1998). Moreover, nonresident fathers tend to bundle their involvement, such that those who see their children frequently also are more likely to be engaged with them, assume parenting responsibility, and provide in-kind support compared to those who see their children infrequently (Coley & Chase-Lansdale, 1999;Ryan, Kalil, & Ziol-Guest, 2008;Kalil, Ziol-Guest, & Coley, 2005;Rangarajan & Gleason, 1998;Sobolewski & King, 2005).…”
Section: Hypothesis 1: Fathers' Proximity Is Beneficial Because It Prmentioning
confidence: 99%